RANCANG BANGUN SISTEM INFORMASI PEMBELIAN PADA CV.CIMANGGIS JAYA DEPOK - Ibnu Rusdi; Ade Sri Mulyani; Inna Herlina (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
Today the rapid development of information technology has a very important role for any company in preparing and processing data. Computer information technology of a set consisting of hardware and software for data processing which can provide any information required and will increase effectiveness, productivity, and efficiency of a company. CV. Cimanggis Jaya is a company range in the field of repair and maintenance services and trading motor vehicle spare parts of motorcycles and cars. In the purchase, calculation of purchases is manually so it can cause the occurrence of human errors. In search and checking data items takes a long time so it is not effective, and if the employee wants to make a purchase report often occur errors. These problems can be avoided by using a computerized system, by making a purchase application program that can speed in completing the work and the company produced accurate data at a faster time.